Analysis of the Characteristics of Natural Materials as Adsorbents in Air Conditioning Adsorption - Aqsal Raja Bramastha; Made Sucipta; Hendra Wijaksana (Natural Sciences Engineering and Technology Journal, 2022)
The use of an air conditioner (AC) increases the use of compressors and electricity supply quite significantly. This will increase global warming and the occurrence of an energy crisis. Referring to this, a cooling system that is more energy-efficient and environmentally friendly is needed. One alternative is to use natural materials as adsorbents in adsorption air conditioning. In this system, changes in humidity levels occur due to the process of absorption of air moisture in each test material in the packed bed. The purpose of this research is to determine the regeneration characteristics of natural materials and activated carbon, as well as their performance against moisture. The characteristics tested also include contact angle test and proximate test. In addition to the type of material, mass variations of 200gr, 400gr, and 600gr are also carried out as well as variations in the combination between materials. The results obtained from the regeneration test 9 times, natural ingredients affect air conditioning. The larger the mass tested, the greater its ability to reduce humidity. In another sense, 600gr activated carbon provides the most optimal performance among other natural materials, both in mass variations and combined variations.